Assessment of Robotic Versus Laparoscopic Distal Gastrectomy for Gastric Cancer: A Randomized Controlled Trial. Issue 5 (May 2021) - Lu, Jun; Zheng, Chao-Hui; Xu, Bin-Bin; Xie, Jian-Wei; Wang, Jia-Bin; Lin, Jian-Xian; Chen, Qi-Yue; Cao, Long-Long; Lin, Mi; Tu, Ru-Hong; Huang, Ze-Ning; Lin, Ju-Li; et al.
Abstract : Objective: To evaluate the short-term outcomes of patients with GC who received RDG or LDG. Summary Background Data: Despite the increasing use of RDG in patients with GC, its safety and efficacy compared to those of LDG have not been elucidated in a randomized controlled trial. Methods: Three hundred patients with cT1-4a and N0/+ between September 2017 and January 2020 were enrolled in this randomized controlled trial at a high-volume hospital in China. The short-term outcomes were compared between the groups. Results: The modified intention-to-treat analysis included data from 283 patients (RDG group: n = 141) and (LDG group: n = 142). Patients in the RDG group exhibited faster postoperative recovery, milder inflammatory responses, and reduced postoperative morbidity (9.2% vs 17.6%, respectively, P = 0.039). Higher extraperigastric lymph nodes (LNs) were retrieved in the RDG group (17.6 ± 5.8 vs 15.8 ± 6.6, P = 0.018) with lower noncompliance rate (7.7% vs 16.9%, respectively, P = 0.006). Additionally, patients in the RDG group were more likely to initiate adjuvant chemotherapy earlier [median (interquartile range) postoperative days: 28 (24–32) vs 32 (26–42), P = 0.003]. Although total hospital costs were higher in the robotic group than in the laparoscopic group, the direct cost was lower for RDG than for LDG (all P < 0.001). Conclusions: RDG is associated with a lower morbidity rate, faster recovery, milder inflammatory responses, and improved lymphadenectomy. Additionally, faster postoperative recovery in the RDG group enables early initiation of adjuvant chemotherapy. Our results provide evidence for the application of RDG in patients with GC. Abstract : Supplemental Digital Content is available in the text